Diverse Motor Performances Are Related to Incident Cognitive Impairment in Community-Dwelling Older Adults - Beeri, Michal Schnaider; Leurgans, Sue E.; Bennett, David A.; Barnes, Lisa L.; Buchman, Aron S. (Frontiers in Aging Neuroscience, 2021)
Objective: Late-life cognitive impairment is heterogeneous. This study examined to what extent varied motor performances are differentially associated with incident Alzheimer’s dementia (AD) and incident mild cognitive impairment (MCI) in older adults. Design: Nested substudy. Setting: Communities across metropolitan Chicago. Participants: African American (N = 580) and European American (N = 580) adults without dementia, propensity-balanced by age (mean = 73.2; SD = 6.0), sex (78.4% women), education (mean = 15.6; SD = 3.3) and number of follow ups. Measurements: Cognitive status was assessed annually and based in part on a composite measure of global cognition including 17 cognitive tests. A global motor score was based on 10 motor performances from which 4 motor domains were computed including hand dexterity, hand strength, gait function, and leg strength. Results: During 7 years of follow-up, 166 of 1,160 (14.3%) developed AD. In a proportional hazards model controlling for age, sex, education, and race, each 1-SD higher baseline global motor score was associated with about a 20% reduction in the risk of AD (hazard ratio: 0.81; 95% CI: 0.68, 0.97). Higher baseline motor function was also associated with decreased risk of incident MCI (hazard ratio: 0.79; 95% CI: 0.68, 0.92). Hand dexterity, hand strength and gait function but not leg strength were associated with incident AD and MCI. When including all four motor domains in the same model, results remained the same for incident MCI, while for incident AD, the association with hand strength remained significant. Conclusion: Diverse motor performances are associated with late-life cognitive impairment. Further work is needed to identify specific motor performances that may differentiate adults at risk for future MCI or AD dementia.